Synthesis of some novel thiourea derivatives obtained from 5-[4-aminophenoxy)methyl]-4-alkyl/aryl-2,4-dihydro-3H-1,2,4-triazole-3-thiones and evaluation as antiviral/anti-HIV and anti-tuberculosis agents - TATAR, ESRA; KÜÇÜKGÜZEL, İLKAY; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2008)
As a continuation of our previous efforts on N-alkyl/aryl-N'-[4-(4-alkyl/aryl-2,4-dihydro-3H-1,2,4-triazole-3-thione-5-yl)phenyl]thioureas 1-19 and N-alkyl/aryl-N'-[4-(3-aralkylthio-4-alkyl/aryl-4H-1,2,4-triazole-5-yl)phenyl]thioureas 20-22, a series of novel 5-[(4-aminophenoxy)-methyl] -4- alkyl/aryl-2,4-dihydro-3H-1,2,4-triazole-3-thiones 23-26 and several related thioureas, N-alky/aryl-N'-{4-[(4-alkyl/aryl-5-thioxo-4,5-dihydro-1H-1,2,4-triazol-3-yl)methoxy]phenyl)thioureas 27-42 were synthesized for evaluation of their antiviral potency. Structures of the synthesized compounds were confirmed by the use of H-1 NMR, C-13 NMR and HR-MS data. All compounds 1-42 were evaluated in vitro against HIV-1 (IIIB) and HIV-2 (ROD) strains in MT-4 cells, as well as other selected viruses such as HSV-1, HSV-2, Coxsackie virus B4, Sindbis virus and Varicella-zoster virus using HeLa, Vero, HEL and E 6SM cell cultures, and anti-tuberculosis activity against Mycobacterium tuberculosis H37Rv. Compounds 4 and 5 showed weak activity against HSV-1, HSV-2 and TK- HSV, whereas eight compounds showed marginal activity against Coxsackie virus B4. The most active derivative in this series was compound 38 which showed moderate protection against Coxsackie virus B4 with an MIC value of 16 mu g/ml and a selectivity index of 5. This compound was also active against thymidine kinase positive Varicella-zoster virus (TK+ VZV, OKA strain) with an EC50 value of 9.9 mu g/ml. Compound 38 was the most active compound with 79% inhibition against M. tuberculosis H37Rv. (c) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: 1,2,4-triazole; thioureas; antiviral activity; anti-tuberculosis activity; REVERSE-TRANSCRIPTASE INHIBITORS; POTENT NONNUCLEOSIDE INHIBITORS; HERPES VIRUSES; PETT COMPOUNDS; PART 1; STEREOCHEMISTRY; EFFICACY; DESIGN; ASSAY